(untitled) (International Journal of Engineering and Computer Science, 2014)
Microstrip has been one of the most popular microwave transmission-line formats for decades and is well characterized. Microstrip circuits find extensive applications in radar systems, microwave communication links, satellite communication systems, wireless and mobile communication systems, medical equipment, etc. In this paper, a model of rectangular patch antenna with two parallel patches is designed and simulated to evaluate the performance. The output results are taken and analyzed for their radiation pattern and transmission losses. The reference/characteristic impedance taken is 50 Ω and the operating frequency domain is.4.5 to 6.7 GHz. The whole microstrip patch antenna is encapsulated in the inert spherical atmosphere of 10 mm thickness containing air inside it